Economic Development of Indigenous Papuans: A Critical Analysis to Build Independent and Dignified Traditional Villages - Fredrik Sokoy (Journal of Social Science, 2022)
Problems within indigenous peoples include issues, such as self-identity, outlook on life, rights to land, forests or natural resources (SDA), claims to traditional territories/territories, and so on. The conceptual unification of the four dominant factors is 'vulnerable' which makes it easier for the existence and roles and demands of indigenous peoples to be marginalized. Discourse on indigenous peoples has been, is temporary, and will continue to take place in Indonesia, as long as their status and rights have not been officially and fully guaranteed by law and implemented by the government, including their involvement in economic development. The results of the study indicate that the model of economic development of indigenous peoples in Papua Province can be carried out through four strategies. First, the recognition and protection of indigenous peoples' rights by the state and local governments. Recognition and protection of the rights of indigenous Papuans by the state and the Papuan Provincial Government. Second, increasing the understanding of indigenous Papuans for their economic development. Indigenous peoples through existing institutions can initiate and manage their economic development process through partnerships with government and non-governmental institutions, such as banks and other banking institutions. Third, the development of the economic capital of indigenous peoples, which consists of customs, belief systems, values, language, culture (traditional tourism, dance and carving), and traditional knowledge in the management and protection of life. Fourth, the development of community-based tourism, in which the Papua Provincial Government needs to involve local indigenous peoples through the recognition of local wisdom possessed by indigenous peoples.